2005
DOI: 10.1111/j.1600-6143.2005.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Living‐Donor Liver Transplantation for Hepatoblastoma

Abstract: Hepatoblastoma is the most common malignant liver tumor in children. Recently, liver transplantation has been indicated for unresectable hepatoblastoma. We retrospectively reviewed 14 children with a diagnosis of hepatoblastoma who had undergone living-donor liver transplantation (LDLT) at Kyoto University Hospital. During the period from June 1990 to December 2004, 607 children underwent LDLT. Of these interventions, 2.3% were performed for hepatoblastoma. Based on radiological findings, the pre-treatment ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 26 publications
(44 reference statements)
0
51
0
Order By: Relevance
“…Total hepatectomy and LTx allow children with unresectable HBL to achieve comparable survival [3,[5][6][7]17,18,[22][23][24][25][26]. The comparison between patients treated with partial liver resection and patients with primary LTx in our center showed that survival rates in both groups are similar (71% vs 80%), but one must acknowledge that patients in both groups are not clinically comparable.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Total hepatectomy and LTx allow children with unresectable HBL to achieve comparable survival [3,[5][6][7]17,18,[22][23][24][25][26]. The comparison between patients treated with partial liver resection and patients with primary LTx in our center showed that survival rates in both groups are similar (71% vs 80%), but one must acknowledge that patients in both groups are not clinically comparable.…”
Section: Discussionmentioning
confidence: 96%
“…In patients with borderline resectability, histopathologic subtype should be defined, and other factors such as AFP concentration and response to the initial 2 courses of chemotherapy on computed tomographic imaging may affect the decision for the selection of the surgical procedure. There is no doubt, however, that for children with PRETEXT IV HBL and no extrahepatic disease, total hepatectomy and LTx are the best options, with good prognosis in about 70% to 80% of children [2,[5][6][7]17,18,22,26]. The most problematic group of patients is a group of children with PRETEXT stage III tumors (2 nonadjoining sections free or just 1 section free; in the latter case, 3 sections are involved).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caval replacement is often required for complete clearance and can be achieved by the use of donor iliac vein interpositional grafts. [24][25][26][27] The use of grafts from living donors offers some potential advantages over cadaveric donation, including shorter waiting time, better graft quality, more rapid recovery, and improved timing of transplant to comply with chemotherapy regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Major multicenter studies by International Society of Pediatric Oncology and German Cooperative Pediatric Liver Tumor Study, such as SIOPEL-1 and HB 94, did not control for differing immunosuppression regimens being used by their participating centers [4,6]. Most single center series by major pediatric liver transplantation centers report their immunosuppression regimen but did not comment on the effect of immunosuppression on their outcomes [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 94%